Survey of Physical Activity and Physical Fitness in Students Aged 14-16 Years - Al Hafiz Saputra; Wahyu Indra Bayu; Destriani Destriani; Herri Yusfi (Sriwijaya Journal of Sport, 2023)
This research aims to determine the level of physical activity and physical fitness in students aged 14-16 years. Quantitative descriptive research was carried out using a survey method which aims to collect data using the Global Physical Activity Questionnaire (GPAQ) instrument and the Indonesian Student Fitness Test (TKPN). The sample used was 89 students using the Slovin formula. The data analysis method uses quantitative descriptive analysis and percentages. using MS Excel facilities. And the results obtained were that the level of physical activity in SMA PGRI 2 Palembang students was categorized as "high", with a percentage of 65.17%. The results of the physical fitness level test for SMA PGRI 2 Palembang students were categorized as "Good", with a percentage of 51.69%. Based on the research conducted, it can be concluded that students at SMA PGRI 2 Palembang have a "high" level of physical activity and a "good" level of physical fitness, because the activities and sports activities carried out by students in everyday life are classified as active and intense.